Assessing the effect of hyperbaric oxygen therapy in breast cancer patients with late radiation toxicity (HONEY trial): a trial protocol using a trial within a cohort design - M. C. T. Batenburg; H. J. G. D. van den Bongard; C. E. Kleynen; W. Maarse; A. Witkamp; M. Ernst; A. Doeksen; T. van Dalen; M. Sier; E. J. P. Schoenmaeckers; I. O. Baas; H. M. Verkooijen (Trials, 2020)
Abstract Background Breast cancer treatment with radiotherapy can induce late radiation toxicity, characterized by pain, fibrosis, edema, impaired arm mobility, and poor cosmetic outcome. Hyperbaric oxygen therapy (HBOT) has been proposed as treatment for late radiation toxicity; however, high-level evidence of effectiveness is lacking. As HBOT is standard treatment and reimbursed by insurers, performing classic randomized controlled trials is difficult. The “Hyperbaric OxygeN therapy on brEast cancer patients with late radiation toxicity” (HONEY) trial aims to evaluate the effectiveness of HBOT on late radiation toxicity in breast cancer patients using the trial within cohorts (TwiCs) design. Methods The HONEY trial will be conducted within the Utrecht cohort for Multiple BREast cancer intervention studies and Long-term evaluation (UMBRELLA). Within UMBRELLA, breast cancer patients referred for radiotherapy to the University Medical Centre Utrecht are eligible for inclusion. Patients consent to collection of clinical data and patient-reported outcomes and provide broad consent for randomization into future intervention studies. Patients who meet the HONEY in- and exclusion criteria (participation ≥ 12 months in UMBRELLA, moderate/severe breast or chest wall pain, completed primary breast cancer treatment except hormonal treatment, no prior treatment with HBOT, no contraindications for HBOT, no clinical signs of metastatic or recurrent disease) will be randomized to HBOT or control group on a 2:1 ratio (n = 120). Patients in the control group will not be informed about participation in the trial. Patients in the intervention arm will undergo 30–40 HBOT treatment sessions in a high pressure chamber (2.4 atmospheres absolute) where they inhale 100% oxygen through a mask. Cohort outcome measures (i.e., physical outcomes, quality of life, fatigue, and cosmetic satisfaction) of the HBOT group will be compared to the control group at 3 months follow-up. Discussion This pragmatic trial within the UMBELLA cohort was designed to evaluate the effectiveness of HBOT on late radiation toxicity in breast cancer patients using the TwiCs design. Use of the TwiCs design is expected to address issues encountered in classic randomized controlled trials, such as contamination (i.e., HBOT in the control group) and disappointment bias, and generate information about acceptability of HBOT. Trial registration ClinicalTrials.gov. NCT04193722 . Registered on 10 December 2019.